Colour and chemical characteristics of patty burger added with red fruit paste (Pandanus conoideus Lamk). Issue 1 (June 2021) - Tharukliling, S; Radiati, L E; Thohari, I; Susilo, A
Abstract: Red fruit is a Papua endemic plant which is rich in bioactive components such as carotene, tocopherol and fatty acids. Red fruit paste (RFP) is a waste from the process of making red fruit oil which is processed using wet rendering and still rich of bioactive component. This study aims to determine the effect of adding red fruit paste on the colour and chemical characteristics beef patties. The colour beef patty observed based formulated by different level of red fruit paste ( Pandanusconoideus Lamk) at 0, 5, 10 and 15% to replace fat animal. The addition of up to 15% red fruit paste to beef patty formulation showed the higher L* (brightness) value and the lower value was the control patty. All red fruit paste-based beef patty enhance colour a* (redness). Higherlevelpaste will made patty became more redness. The addition red fruit paste in 5% had higher b* (yellowness) value, on theotherhandparameter of chemical characteristic of beef patty was compared with patty control treatment and patty with 15% level RFP was the best colour result. The data took before and after cooked. The protein content before and after cooking had a higher value by control treatment but for the value of fat, carbohydrate, water, ash and carotene content in the patty with 15% RFP the value was higher than the control both before and after cooking.